Editorial [Hot Topic: Therapeutic Approaches for Vision Loss due to Choroidal Neovascularizations in Age Related Macular Degeneration (Guest Editor: Ciro Costagliola)] - Costagliola, Ciro (Current Drug Targets, 2011)
The Literature Search using as keyword “Age Related Macular Degeneration” (AMD) has identified more than 13,000 articles in Medline from 1960 to 2009. This apparently high number of articles, which surely does not account for the importance of the disease, became plethoric in the last decade, with more than two-thirds of totally published papers. AMD represents the leading cause of blindness in industrialized countries in people aged 65 years or older. Even in developing nations, AMD is gaining attention due to increased life expectancy and improved visual care facilities. The clinical presentation of AMD ranges from a few soft drusen and normal visual acuity to subfoveal choroidal new vessels (CNV) with disciform scarring and legal blindness. Rarely, patients have profound visual loss caused by extensive subretinal and vitreous hemorrhage [1]. It initially occurs in a “dry” or atrophic form, and can progress to geographic atrophy or convert to exudative or “wet” AMD, characterized by CNV [2]. The prevalence of AMD markedly increases with aging, but it is uncommon before the age of 50 years, whereas by age 90, one in four persons will sure to lose vision [3]. The natural course of AMD varies extremely between individuals. However, reliable factors for the explanation of this variability have so far not been established. The substantial variety in presentation, natural history of progression and associated risk factors suggest that several phenotypes of AMD may exist and different patterns of disease progression and functional impairment may reflect distinct underlying aetiologies. While our understanding of molecular events presaging AMD has grown in the last decade, its pathogenesis is yet a conundrum. In fact, genetic factors, oxidative stress, hydrodynamic changes, senescence of retinal pigment epithelium, hemodynamic changes, angiogenesis and subclinical inflammation [4] have been -from time to time- considered as the primum movens of the disease. The study of AMD pathogenesis as well as the therapeutic advances are hampered by the absence of an animal model that faithfully resembles every phase of AMD. The primary locus of insult for Age-Related Macular Degeneration remains in dispute. The hallmarks of the disease are; diffuse and focal thickening of Bruch's membrane (drusen) together with the development of hypo- and hyper-pigmented areas of RPE, the former signifying areas of RPE cell loss [5]. Although an array of risk factors has been epidemiologically related to AMD, their role in the progression of the disease remains unclear. Still, thanks to a greater understanding of AMD aetiology therapeutic strategies which have been moved beyond the initial limited approach of thermal laser photocoagulation. Photodynamic therapy with verteporfin (PDT-V) represents such a milestone in new options, but it too has restricted benefits. The therapeutic effect of PDT-V is achieved by a laser-light-induced thrombosis of CNV that has been photosensitized by the administration of verteporfin [6]. The individually variable efficacy of standardized PDT-V is clearly noticeable by reviewing the outcomes of Treatment of Age-Related Macular Degeneration with Photodynamic Therapy (TAP), Visudyne in Photodynamic Therapy (VIP), and Visudyne in Minimally Classic Choroidal Neovascularization studies [7-9]. Several gene mutations can affect the balance between pro and anticoagulant mechanisms, accounting for the occurrence of thrombophilic or hemorrhagic diatheses. The therapeutic effect of PDT-V is based on a photochemical perturbation of the hemostasis and coagulation within the neovascular complex. However, only recently the presence of a predictive correlation between peculiar coagulation-balance gene polymorphisms and different levels of PDT-V responsiveness in AMD patients with classic or predominantly classic CNV has been documented. These findings have provided a pharmacogenetic relationship between coagulation-balance genetic backgrounds and different levels of PDT-V effectiveness [6, 10-13]. Triamcinolone acetonide (TA) has been the first compound used for the treatment of CNV secondary to AMD. TA modulates the permeability and adhesion of in vitro cultured endothelial cells, down-regulates cytokine-induced expression of the intercellular adhesion molecule, as well as the matrix metalloproteinase and interferon gamma-induction of vascular permeability [14]. Lastly, Ciulla et al. have shown that triamcinolone inhibited laser-induced choroidal neovascularization in rats [15]. TA has the peculiar characteristics of being safe and well tolerated by the ocular tissues and consistently effective, thanks to its capability to remain active for many months after a single intravitreal injection. In the past decade, intravitreal injection of TA (IVTA) has emerged as a useful treatment for several ocular diseases such as uveitis, macular oedema secondary to retinal vasculature disease, neovascularization and vitreous-retinopathy. IVTA treatments may slow down the natural course of AMD. No significant improvement of visual functions has been recorded in patients with exudative AMD, whereas a decrease of leakage in fluorescein angiography (FA) and a lack of further loss in visual functions have occurred. However, in the long-term follow-up IVTA as monotherapy had no effect on the risk of severe visual acuity loss, despite a significant anti-angiogenic effect was observed in the short-term follow-up. Consequently, the synergistic combination of IVTA with photodynamic therapy (PDT), has been reported to improve vision and to reduce the number of PDT re-treatments [16]. Intraocular pressure (IOP) elevation has been reported in 19%- 43% of eyes after IVTA. It occurs most often between one and three months after the injection. Jonas et al. [17] reported IOP greater than 21, 30, 35 and 40 mmHg in 41.2%, 11.4%, 5.5% and 1.8% patients, respectively. Rise in IOP is well controlled with one or two topical anti-glaucoma medications; approximately 3% needs filtering surgery. The introduction of anti-vascular endothelial growth factor (VEGF)-based drugs has revolutionized the treatment of AMD and has replaced all the previous therapies used for CNV. Visual improvement becomes an expectation in a high proportion of patients, previously limited to minimizing vision loss. Multiple studies have suggested that VEGF increases vascular permeability and is involved in the pathogenesis of neovascularization in human eye disease [18]. Current approaches to inhibit VEGF involve binding it to a molecule that prevents receptor 0-ligand interaction, thus incapacitating the effect of VEGF on the local environment. Options currently include either a full-length recombinant monoclonal antibody (bevacizumab), a humanized antibody fragment (ranibizumab), or a pegylated aptamer (pegaptanib sodium). Anti-VEGF therapies are an important breakthrough in exudative AMD, but they present issues that need to be explained. First, the risk for the development of endophthalmitis, which - although not so high - represents a potential devastating complication. Second, the rate of treatment, which presumes to be a monthly administration. Third, the cost of treatment, directly due to the compound and indirectly due to the need to re-examine the patient at each check. Fourth, the potential to develop cardiovascular and cerebral acute accident following prolonged exposure to anti VEGF drugs; in fact, these compounds have many essential functions, including the formation of collateral vessels after ischemia, as well as neurotrophic properties. Despite intra-vitreous injection, systemic absorption occurs and long-term treatment with repeated injections may cause chronic inhibition of the VEGF and its associated adverse effects [19]. Lastly, the resistance to anti-angiogenic therapy, i.e. why some patients do not respond to the treatment. Treatments for CNV can target either the vascular components of CNV (the new vessels that proliferate and leak blood and fluid) or the angiogenic components (that lead to the development of the condition). The combination of vPDT, (targeting the vascular components) and the anti-VEGF therapy (targeting key mediators of the angiogenic cascade), may have an additive or synergistic effect in reducing the frequency of treatment [20]. Moreover, the expression of VEGF is increased after PDT therapy and contributes to the re-growth of CNV. The combination therapy may be a cost effective alternative to monotherapy by reducing the need for re-treatment. A meta-analysis of randomized clinical trials comparing approved pharmacological treatments for neovascular AMD has shown that ranibizumab was the most effective treatment compared to PDT and pegaptanib....